RESEARCH ON PERSONALITY SELF-REALIZATION IN CONTEXT OF SYSTEMIC PARADIGM - S I Kudinov; S S Kudinov; S R Aybazova; K G Marin Jerez (Peoples' Friendship University of Russia (RUDN University), 2015)
The article is devoted to the problem of the systematic conditionality of personality self-realization. It substantiates the prospects of a systematic approach to the study of this phenomenon, as opposed to the well-established analytical strategies in Russian and foreign psychology. System components and structural characteristics of the self-realization are provided.